Robust Monotone Iterates for Nonlinear Singularly Perturbed Boundary Value Problems. (14th May 2009) - Boglaev, Igor
Abstract : This paper is concerned with solving nonlinear singularly perturbed boundary value problems. Robust monotone iterates for solving nonlinear difference scheme are constructed. Uniform convergence of the monotone methods is investigated, and convergence rates are estimated. Numerical experiments complement the theoretical results.